Biomedical implications of viral mutation and evolution. (April 2012) - Sanjuán, Rafael; Lázaro, Ester; Vignuzzi, Marco
Mutation rates vary hugely across viruses and strongly determine their evolution. In addition, viral mutation and evolution are biomedically relevant because they can determine pathogenesis, vaccine efficacy and antiviral resistance. We review experimental methods for estimating viral mutation rates and how these estimates vary across viral groups, paying special attention to the more general trends. Recent advances positing a direct association between viral mutation rates and virulence, or the use of high-fidelity variants as attenuated vaccines, are also discussed. Finally, we review the implications of viral mutation and evolution for the design of rational antiviral therapies and for efficient epidemiological surveillance.